Why should we be called 'coolies'? - Mahase, Radica, author.
1 online resource
Keywords: What are the dynamics of the abolition of the Indian indentureship system? Why was it ended? Who were the main players in the final end of the labour scheme? Were Indian labourers and/or the Indian middle classes actively involved in the processes leading towards complete abolition? This book examines the end of a labour system which lasted from 1838 until 1920 in various territories throughout the British Empire. It looks at methods of agitations which had their genesis in the territories of the Indian Ocean and compare/contrast these with those of other territories such as the British West Indies.The volume provides a comparative study of the abolition of the Indian indentureship system and shows the global interconnectedness of abolition, with a strong subaltern focus. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.